Cardiac Radionuclide Imaging in Rodents: A Review of Methods, Results, and Factors at Play - Cicone, Francesco; Viertl, David; Quintela Pousa, Ana Maria; Denoël, Thibaut; Gnesin, Silvano; Scopinaro, Francesco; Vozenin, Marie-Catherine; Prior, John O. (Frontiers in Medicine, 2017)
The interest around small-animal cardiac radionuclide imaging is growing as rodent models can be manipulated to allow the simulation of human diseases. In addition to new radiopharmaceuticals testing, often researchers apply well established probes to animal models, to follow the evolution of the target disease. This reverse translation of standard radiopharmaceuticals to rodent models is complicated by technical shortcomings and by obvious differences between human and rodent cardiac physiology. In addition, radionuclide studies involving small animals are affected by several extrinsic variables, such as the choice of anesthetic. In the present paper, we review the major cardiac features that can be studied with classical single-photon and positron-emitting radiopharmaceuticals, namely cardiac function, perfusion and metabolism, as well as the results and pitfalls of small-animal radionuclide imaging techniques. In addition, we provide a concise guide to the understanding of the most frequently used anesthetics: ketamine/xylazine, isoflurane and pentobarbital. We address in particular their mechanisms of action and the potential effects on radionuclide imaging. Indeed, cardiac function, perfusion and metabolism can all be significantly affected by varying anesthetics and animal handling conditions.